Visits to Cajamarca in 1571-1572 and 1578 as a source for linguistic studies - Andrade Ciudad, Luis (2021)
In 1992, two volumes were published detailing the visits to Cajamarca in 1571-1572 and 1578. These contain important social, demographic and onomastic information for the linguistic history of the northern Peruvian Andes. Although the edition focused on the exhaustive record of the indigenous people from Bambamarca, Pomamarca andChondal made by the visitors, the complete dossier was not included in the publication. In this paper we propose to briefly describe the contents of the missing parts, which provides a better understanding of the context in which the visits took place. We also show that thesource of this publication is a transfer from another, as yet unknown, document. Taking the latter into account, we ponder the advantages and limitations of these visits as a source for studies on historical linguistics in the Andes.